Edukasi Bahaya Child Grooming kepada Anak di Bawah Umur - Formas Juitan Lase (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
The data from Indonesian Ministry of Women Empowerment and Child Protection shows that the children that aged between 13-17 years are the most vulnerable ones to sexual violences. One of the most dangerous cases and hotly discussed in the field is the child grooming or child sexual grooming. This violence is perpetrated by adults against children by building trust and emotional relationships so that it is easier for perpetrators to manipulate, exploit, and harass the victims. In order to tackle the rise of this kind of violence, it is necessary to educate the potential victims especially the children. This socialization program was conducted for students of SMPN 279 Jakarta. With the proper knowledge related to sexual violence example such as child grooming, the children can recognize the grooming behavior and can prevent them from becoming victims.